2017
DOI: 10.1103/physrevlett.118.167401
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Nonlinearity Generated from Electromagnetic Coupling Metamolecule

Abstract: A purely artificial mechanism for optical nonlinearity is proposed based on a metamaterial route. The mechanism is derived from classical electromagnetic interaction in a meta-molecule consisting of a cut-wire meta-atom nested within a splitring meta-atom. Induced by the localized magnetic field in the split-ring meta-atom, the magnetic force drives an anharmonic oscillation of free electrons in the cut-wire metaatom, generating an intrinsically nonlinear electromagnetic response. An explicit physical process … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 36 publications
0
38
0
Order By: Relevance
“…Namely, the non-Kramers Pr ions feel the linear transversefield terms from random impurities in Pr 2 Zr 2 O 7 . 37,38) Both of the linear and bi-linear terms could exist in reality, and the cleaner samples would have the stronger bilinear couplings. The QSL can be even stabilized under the presence of impurities.…”
Section: Resultsmentioning
confidence: 99%
“…Namely, the non-Kramers Pr ions feel the linear transversefield terms from random impurities in Pr 2 Zr 2 O 7 . 37,38) Both of the linear and bi-linear terms could exist in reality, and the cleaner samples would have the stronger bilinear couplings. The QSL can be even stabilized under the presence of impurities.…”
Section: Resultsmentioning
confidence: 99%
“…Amongst the rare earth pyrochlores, several candidate materials have been identified as possessing many of the requisite ingredients, including: Tb2Ti2O7 (29), Yb2Ti2O7 (30), and Pr2Zr2O7 (31). While quantum spin ice ground states in these materials remain tantalizingly close, recent experimental studies show rich low temperature phenomenology including strong sensitivity to quenched impurities (32)(33)(34), which complicates a simple categorization of their ground states.…”
Section: Figurementioning
confidence: 99%
“…At the same time, this can also expand the scope of metamaterials and develop the design methods of metamaterials. Zhou et al pioneered this idea by introducing ferromagnetic materials and Mie resonance into metamaterials or photonic crystal to realize negative permeability or refraction [9][10][11]. Peng et al observed the negative electromagnetic parameters in amorphous-metal sensors and transducers, a great success of multifunctionalization of the devices [12,13].…”
Section: Introductionmentioning
confidence: 99%